Lovell's gazetteer of British North America : containing the latest and most authentic descriptions of over 7,500 cities, town, villages and places, in the provinces of Ontario, Quebec, Nova Scotia, New Brunswick, Prince Edward Island, Manitoba, British Columbia, the North West Territories, and Newfoundland - Crossby, P. A. (Peter Alfred), 1842- editor.; Lovell, John, publisher.; Crossby, P. A. (Peter Alfred), 1842- ed. (Montreal : J. Lovell & son, 1881)
Key to the Railroad and steamboat routes. -- Table of routes. -- Gazetteer. Mode of access: Internet.